Correlation Between Family Financial Status and Recurence Frequency of Schizophrenia at Grhasia Mental Hospital, Yogyakarta - Pipin Cahyati; Budi Prasetyo; Andi Kartikasari Sukma Praja (Kirana Publisher (KNPub), 2026)
The aim of this study is to find out the correlation between family financial status and frequency of schizophrenia recurrence at Grhasia Mental Hospital, Yogyakarta. This research is classified as quantitative, employing a correlational design with a cross-sectional approach. Accidental sampling was employed in determining the respondents. There were 94 respondents in this research, and Kendall Tau was used to analyze the data. The correlation coefficient between variables was p-value=0.007<0.05. It showed that there was a correlation between variables. A strong negative correlation between variables occurred at -0.257. It meant that the lower the financial status, the higher the frequency of recurrence can be. There was a correlation between family financial status and the frequency of a patient's schizophrenia recurrence in Grhasia Mental Hospital, Yogyakarta. The patient's family is suggested to prevent the recurrence by finding out more information to be able to lessen the family burden.